2024
DOI: 10.1021/acs.jpca.3c05882
|View full text |Cite
|
Sign up to set email alerts
|

Self-Consistent Field Approach for the Variational Quantum Eigensolver: Orbital Optimization Goes Adaptive

Aaron Fitzpatrick,
Anton Nykänen,
N. Walter Talarico
et al.

Abstract: We present a self-consistent field (SCF) approach within the adaptive derivative-assembled problem-tailored ansatz variational quantum eigensolver (ADAPT-VQE) framework for efficient quantum simulations of chemical systems on near-term quantum computers. To this end, our ADAPT-VQE-SCF approach combines the idea of generating an ansatz with a small number of parameters, resulting in shallow-depth quantum circuits with a direct minimization of an energy expression that is correct to second order with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…The orbital-optimized unitary coupled cluster (oo-UCC) method is a recently developed, chemistry-inspired ansatz for the wave function on a quantum computer. Its classic counterpart is the wave function obtained via the multiconfigurational self-consistent field (MCSCF) method . Just like MCSCF, oo-UCC splits the full space into smaller subspaces.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The orbital-optimized unitary coupled cluster (oo-UCC) method is a recently developed, chemistry-inspired ansatz for the wave function on a quantum computer. Its classic counterpart is the wave function obtained via the multiconfigurational self-consistent field (MCSCF) method . Just like MCSCF, oo-UCC splits the full space into smaller subspaces.…”
Section: Theorymentioning
confidence: 99%
“…The energy of the ground state can now be found by variational minimization in the parameters θ and κ , E normalg normals = min bold-italicθ , bold-italicκ normalU normalC normalC false( bold-italicθ false) false| ( κ ) false| normalU normalC normalC false( bold-italicθ false) Here, false| U C C = exp ( false( bold-italicθ false) ) false| C S F . Performing this minimization process on quantum architecture is known as the orbital-optimized variational quantum eigensolver (oo-VQE) algorithm. Its major advantage is splitting the problem into the active space simulations on the quantum computer and performing all operator applications outside the active space, i.e., the orbital rotations, classically.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In the following, we introduce the PE-VQE-SCF formalism, developed by Kjellgren et al, which builds upon the ADAPT-VQE-SCF method originally developed by Fitzpatrick et al Further information can also be found in ref . We begin by expressing the spin-free, nonrelativistic, electronic Hamiltonian in second quantization as = prefix∑ p q h p q p q + 1 2 p q r s g q p r s ( p q r s δ q r p s ) where Ê pq is again a singlet one-electron excitation operator and h pq and g pqrs are, respectively, the one- and two-electron integrals over the molecular orbitals ϕ p ( r ): h p q = prefix∫ ϕ p * ( r ) ϕ q ( r ) .25em normald boldr g p q r s = prefix∫ ϕ p * ( r 1 ) ϕ r * …”
Section: Theorymentioning
confidence: 99%
“…In this paper, we will use the implementation of the PE model for quantum computers in combination with the adaptive derivative-assembled problem-tailored ansatz variational quantum eigensolver self-consistent field approach (ADAPT-VQE-SCF) and test its performance on calculating the EFGs of ice VIII and ice IX. We aim to reproduce the experimental results with conventional CASSCF and the ADAPT-VQE-SCF approach on a quantum simulator for ice VIII and ice IX.…”
Section: Introductionmentioning
confidence: 99%